Role of surgical simulation to enhance the knowledge of surgical procedures - Singh, Deepak Raj; Regmee, Sujan; Chakradhar, Rupesh; Agrawal, Aditi; Bhujel, Kshitiz; Gurung, Susant; Laudari, Uttam; Bohara, Tanka Prasad (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Surgical simulator is a computer based technology used to educate and train medical students and practitioners without the need for a patient, cadaver or an animal model. Touch surgeryTM(TS) is a free of cost smartphone based application used for teaching surgical procedures. The participants in this study were specifically assessed on the increase of their knowledge in the key steps of laparoscopic cholecystectomy after practicing on the smartphone simulator, TS. Methods: A non-randomized controlled trial (uncontrolled longitudinal study) was carried out among 20 final year medical students. Their knowledge on surgical procedure was assessed through a questionnaire prepared regarding the steps of laparoscopic cholecystectomy before and after exposure to TS. Study Variable was the scores to a questionnaire before and after exposure to the surgical simulation. Results: Mean pre-practice score was 25.85 ± 11.05 and mean post practice score was 80 ± 10.62 (p<0.001). Conclusion: This study suggests that the use of TS can increase the knowledge of the students about laparoscopic cholecystectomy. This can definitely be used for teaching students, other surgical procedures.